ANALISIS KUAT TEKAN BETON DENGAN VARIASI AIR DARI BERBAGAI SUMBER DI KALIMANTAN SELATAN - Husnul Khatimi (Universitas Lambung Mangkurat, 2014)
Water is one of the elements forming the fresh concrete mix is crucial. Therefore, SNI 03-2847-2002 arranged that water can be used as concrete mix is water that qualifies as drinking water. However, with abundant water reserves near the project site, implementers often take water in the environment to be used as a mixture of concrete. Notwithstanding this water use water that meets the requirements. Therefore it is important to know how to influence the use of this water when used as an ingredient in the concrete. The water used in this study originated from PDAM, brackish estuary area Barito, Peat in the area Sambang Lihum, Martapura River, Polder Alabio, and wells in the area Banjarbaru. Concrete will be tested for compressive strength at 28 and 56 days.The test specimen cube measuring 50 mm and standard cylinders made respectively of 36 pieces. 18 fruits tested at 28 days and the remaining 18 units were tested at the age of 56 days. The test specimen made of compressive strength with maximum load parameters or until the concrete collapse.Specimens with water sourced from PDAM and from the river has over 25 MPa compressive strength. Whereas specimens with different water source does not reach the compressive strength. Even with the use of brackish water, compressive strength was not achieved until 10 Mpa. Keywords: concrete compressive strength, water brackish water and peat